RISK MANAGEMENT IN TRANSLATION - BOOK REVIEW - Antony Hoyte-West (English Studies at NBU)
Book Details: Title: Risk Management in Translation Author: Anthony Pym Publisher: Cambridge University Press Number of pages: 76 pages Year of publication: 2025 ISBN: 9781009546843 (hardback) Also available as: ISBN 9781009546874 (paperback), ISBN 9781009546836 (eBook)